Inhibition of UGT1A1*1 and UGT1A1*6 catalyzed glucuronidation of SN-38 by silybins. (1st December 2022) - Li, Wei; Chen, Yin-Nan; Chen, Yue-Yue; Wang, Zhe; Wang, Zhen; Jiang, Li-Li; Shi, Hong-Can; Liu, Yong
Abstract: UGT1A1 is the main enzyme that catalyzes the metabolic elimination and detoxification of SN-38, the active form of the drug irinotecan. Milk thistle products have been used widely to protect the liver from injury associated with the use of chemotherapeutic agents. To evaluate whether SN-38 metabolism can be affected by milk thistle products, the inhibitory effects of silybins on UGT1A1*1 and UGT1A1*6 were evaluated in the present investigation. Both silybin A and silybin B potently inhibited SN-38 glucuronidation catalyzed by UGT1A1*1 or UGT1A1*6. It was noteworthy that silybin A and silybin B showed synergistic effect in UGT1A1*1 microsomes at concentration around IC50, while additive effect in UGT1A1*6. According to the predicted AUCi /AUC ratios (the ratio of the area under the plasma concentration–time curve of SN-38 in the presence and absence of silybins), the coadministration of irinotecan and several milk thistle products, including silybin-phosphatidylcholine complex, two Legalon capsules, four Silymarin tablets or four Liverman capsules, may lead to clinically significant herb-drug interactions (HDI) via UGT1A1 inhibition. Meanwhile, Rgut values were much higher than 11 in all the groups, indicating potential HDI due to intestinal UGT1A1 inhibition. Highlights: Silybins can inhibit SN-38 glucuronidation catalyzed by UGT1A1*1 or *6. Silybin A and B can synergistically inhibit UGT1A1*1 at concentration around IC50 . Silybin A and B can additively inhibit UGT1A1*6 at concentration around IC50 . Potential HDI may occur via hepatic and intestinal UGT1A1 inhibition.